2018
DOI: 10.1016/j.nicl.2018.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Disrupted brain network topology in chronic insomnia disorder: A resting-state fMRI study

Abstract: This study investigated the topological characteristics of brain functional networks in chronic insomnia disorder (CID) patients. The resting-state functional magnetic resonance imaging and graph theory analysis method were applied to investigate the brain functional connectome patterns among 45 CID patients and 32 healthy controls. The brain functional connectome was constructed by thresholding partial correlation matrices of 90 brain regions from an automated anatomical labeling atlas. The topologic properti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
52
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(55 citation statements)
references
References 58 publications
3
52
0
Order By: Relevance
“…In this review, inadequate sleep was strongly associated with neuroanatomical structures and functions of the developing adolescent brain. Similarly, structural alterations in multiple brain regions have been found in adults with sleep problems, mainly those with primary insomnia [26][27][28][29][30] . These alterations have appeared mainly in the hippocampus, orbitofrontal cortex, and frontal and middle temporary gyri 31 .…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…In this review, inadequate sleep was strongly associated with neuroanatomical structures and functions of the developing adolescent brain. Similarly, structural alterations in multiple brain regions have been found in adults with sleep problems, mainly those with primary insomnia [26][27][28][29][30] . These alterations have appeared mainly in the hippocampus, orbitofrontal cortex, and frontal and middle temporary gyri 31 .…”
mentioning
confidence: 97%
“…These alterations have appeared mainly in the hippocampus, orbitofrontal cortex, and frontal and middle temporary gyri 31 . Additionally, a growing body of functional neuroimaging studies have demonstrated the relationship between aberrant regional brain activities and sleep problems, with sex differences across the whole brain 29,32 .…”
mentioning
confidence: 99%
“…Subsequently, the directed and weighted functional connectivity matrices were constructed using GraphVar Software ( Kruschwitz et al, 2015 ) ( Figure 3B ). The topologic properties of brain functional network were measured at both global and nodal levels with constructed connectivity matrices ( Li et al, 2018 ). At the global level, brain network topologic balance was determined by functional segregation and functional integration.…”
Section: Methodsmentioning
confidence: 99%
“…However, it should be noted that brain alterations in ID may be more complex and involve other connections. For example, resting-state fMRI studies show that there are functional disruptions in ID patients, such as disruptions in global and regional topological organization of the brain functional connectome, including the dorsal attention, default mode, and sensory-motor networks (Li et al, 2018).…”
Section: Introductionmentioning
confidence: 99%